“HUTAN ADAT” (INDIGENOUS FORESTS) AS A MODEL FOR SUSTAINABLE FOREST GOVERNANCE: A CASE STUDY OF THE DAYAK COMMUNITY IN BORNEO - Wijaya Wijaya; Sakura Suzuki; Haruka Sato (Yayasan Adra Karima Hubbi, 2025)
Escalating deforestation and the shortcomings of conventional, state-centric forest management paradigms necessitate the exploration of alternative governance models. Hutan Adat (Indigenous Forests), managed through customary laws, represent a long-standing yet frequently overlooked approach to ecological stewardship. This research aims to analyze the principles and practices of Hutan Adat management by the Dayak community in Borneo, evaluating its effectiveness and potential as a replicable model for sustainable forest governance. Employing a qualitative case study approach, this study utilizes ethnographic observation, in-depth interviews with community elders, and participatory mapping. The findings reveal a sophisticated governance system rooted in local wisdom, spiritual values, and collectively enforced customary laws (hukum adat). This system effectively regulates resource extraction, conserves biodiversity, and ensures equitable benefit sharing, resulting in lower deforestation rates and greater ecological integrity compared to adjacent state-managed areas. The study concludes that the Dayak Hutan Adat is a robust and effective model of sustainable forest governance. Its formal recognition and integration into national policy frameworks are crucial for achieving conservation goals while upholding indigenous rights and promoting social justice.